Impact of Safety Risk Defense Mechanism in Operating Room Nursing on Quality and Risk Incidents - Liao H; Lou L (Risk Management and Healthcare Policy, 2025)
Haiyan Liao, Lihua Lou Department of Chiropractic, Guangfu Hospital, Jinhua, Zhejiang, People’s Republic of ChinaCorrespondence: Haiyan Liao, Email yspv840@163.comObjective: To explore the application effect of a nursing model based on safety risk defense mechanism management in operating room nursing and its impact on nursing quality and the occurrence of risk incidents.Methods: From November 2022 to December 2023, 200 patients who underwent surgical treatment and received nursing care in the operating room of our hospital were selected as research subjects. During this period, the nursing model in our hospital’s operating room was changed. Based on the time differences, the patients were divided into a control group and an observation group, with 100 cases in each group. The control group adopted the previous conventional nursing model, while the observation group adopted the nursing model based on safety risk defense mechanism management. The nursing quality scores and the occurrence of risk incidents were compared between the two groups.Results: The nursing quality scores of the observation group were significantly higher than those of the control group, P< 0.05. The management effect of the observation group was significantly better than that of the control group, with higher satisfaction and lower complaint rates, P< 0.05. The occurrence rate of risk incidents in the observation group was significantly lower than that in the control group, P< 0.05. The scores in various aspects of risk control in the observation group were significantly higher than those in the control group, P< 0.05.Conclusion: The nursing model based on safety risk defense mechanism management can significantly improve the quality of operating room nursing, reduce the occurrence of nursing risk incidents, and enhance patient satisfaction. It is worthy of clinical promotion and application.Keywords: safety risk defense mechanism management, nursing, model, operating room nursing, application, nursing quality, risk incidents